THE IMPROVING STUDENTS’ WRITING SKILLS IN DESCRIPTIVE TEXT BY USING VISUAL-SPATIAL INTELLIGENCE STRATEGY AT MTS AL-JUMHURIYAH SEI ROTAN - Bulan, Bulan (BRIGHT VISION Journal of Language and Education, 2022)
This research was aimed to find out the improving students’ writing skills in descriptive text by using Visual Spatial Intelligence. in enhancing this research, the researcher applied the classroom action research, which was done through four steps. They were plan, action, observation, and reflection n. The subjects of this study were 19 students at eight grade students of MTS Al Jumhuriyah Sei Rotan in 2019/2020 Academic Year. The technique of analyzing the data of this research was applied by quantitative and qualitative data. The qualitative data were taken from observation sheet, interview, and documentation. The quantitative data were taken  from students writing skill test. The data was taken from test result which was done in two cycles and two cycles conducted in four meetings. The test was given to the students in form of pre-test, post test in the first cycle and the post test in the second cycle. The result of the analyzing the data showed that the students’ mean score was an improving on the students writing skills from each cycles. It was showed from Pre-test, there was 6 students got successful score criteria or it was (32%) and 13 students’ got unsuccessful score criteria. In the Post test in cycle I, there was 10 students (47%) who got successful score criteria. In the post test in cycle II there was 16 students (84%) who got successful score criteria. In Other words, the students’ writing skills in descriptive text was improved. Based on the observation sheet, interview, and documentation, it can be showed that the expression and enthusiasm of students in learning were also improve.